Cast iron corrosion protection with chemically modified Mg Al layered double hydroxides synthesized using a novel approach - Vieira, D.E.L. (2020)
Layered double hydroxides (LDHs) intercalated with corrosion inhibitive species are considered as promising additives to protection coatings. However, the conventional method of LDH preparation via co-precipitation followed by anion exchange is a water consuming and slow process hardly applicable to industrial use. In this work, a novel approach to LDH synthesis via hydration of sol-gel prepared mixed metal oxides and two-step anion exchange, all assisted by high-power sonication, was applied. Mg—Al and Mg-Al-Ce LDH with cations ratios 2:1 and 2:0.9:0.1, respectively, intercalated with corrosion inhibitive dihydrogen phosphate anion were successfully prepared. The obtained LDH were characterized by X-ray diffraction and scanning transmission electron microscopy. Anion release from these LDH in NaCl solutions and their corrosion inhibitive action on cast iron samples were monitored by electrochemical impedance spectroscopy. The results show that the dihydrogen-phosphate-intercalated LDHs produced using the novel technique are efficient in corrosion protection.